Impacto dos problemas farmacoterapêuticos sobre o tempo de internação hospitalar de pacientes puérperas com pré-eclâmpsia - Goes, Aline Santana (2022)
Introduction: few studies assess the nature and prevalence of drug-related problems (DRPs) in hospitalized pregnant women, as well as studies on the impact of DRPs on hospitalized puerperal women are scarce. Thus, studies in this population may promote patient safety by avoiding undesirable outcomes. Aim of the study: to investigate the impact of DRPs on the length of hospital stay of postpartum women with pre-eclampsia. Methods: a prospective cohort study with postpartum women diagnosed with preeclampsia was carried out to determine the relationship between the manifestation of DRPs and length of hospital stay, followed by a systematic review to determine risk factors for prolonged hospital stay in postpartum women with preeclampsia. Finally, a research letter was developed to discuss the active search for manifested DRPs and medication review in hospitalized patients with preeclampsia. Results and Discussion: 600 women were included in the present study, of these 354 (59%) were exposed to at least one DRP. The most frequent DRPs were non-administration of a medication, non-prescription of a medication. In patients exposed to DRPs, the mean hospital stay was 5.4 (SD 3.6) days versus 4.4 (SD 3.3) days in patients not exposed to DRPs (p = 0.0001). In the systematic review, 1,662 studies were identified in the databases, four of which were included in the final sample. The main risk factors for the increase in length of hospital stay were: presence of ascites (p<0.001), cesarean delivery (p<0.0001), presence of manifested DRPs (p=0.0001), diastolic blood pressure above 10mmHg (p=0.006) and treatment time with MgSO4 equal or greater than 12 hours (0.014). All included studies presented a cohort design, with an overall methodological quality classified as good. To have a significant impact on length of hospital stay, as well as other hospital outcomes, medication review should focus on resolving manifested DRPs. In postpartum women with preeclampsia, this intervention should preferably take place in the first days after delivery. Conclusion: the manifestation of DRPs in postpartum women with preeclampsia significantly increased the length of hospital stay, being a main risk factor for alteration of this important hospital outcome. Medication review is a clinical pharmaceutical service that identifies and resolves these events, and has, therefore, the potential to decisively impact the clinical outcomes related to hospitalized postpartum women with preeclampsia.